Monetary policy, debt maturity structure and corporate investment efficiency: Evidence from China - Liping Zheng; Guangzhen Liu; Ziwei Liang; Chengyi Liu (PLoS ONE, 2025)
This paper examines the impact of monetary policy on corporate investment efficiency from the perspective of debt maturity structure by selecting data on Chinese non-financial listed firms and Chinese macroeconomic data from 2007–2022. The results find that loose monetary policy can have a dual effect on corporate investment efficiency by extending corporate debt maturity structure, which is manifested in alleviating corporate under-investment and promoting corporate over-investment. Heterogeneity analysis shows that in high bank competition areas, the debt maturity structure effect of monetary policy is effective in mitigating under-investment and promoting over-investment by enterprises. In contrast, in low bank competition regions, the debt maturity structure effect of monetary policy promotes corporate over-investment but has no significant effect on corporate under-investment. In addition, the debt maturity structure effect of monetary policy can effectively alleviate under-investment and promote over-investment of enterprises with low financing constraints. And it has no significant effect on the under-investment and over-investment behavior of high financing constraint enterprises. The research in this paper reveals the specific mechanism of monetary policy affecting the investment efficiency of enterprises, which has certain reference value for the objective evaluation of monetary policy effects.